الدور الوسيط للضجر في العلاقة بين إدمان الإنترنت وكل من الاكتئاب والقلق والضغط النفسي لدى طلاب الجامعة - هدى عنتر عبدالله قنديل; الشيماء إبراهيم محمد حسب الله (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
هدف البحث الحالي إلى تعرّف التأثيرات المباشرة وغير المباشرة  بين الضجر (متغير وسيط)، وإدمان الإنترنت (متغير مستقل)، والاكتئاب والقلق والضغط النفسي (متغيرات تابعة) لدى طلاب الجامعة، ومدى اختلاف كل من: الضجر، وإدمان الإنترنت، والاكتئاب والقلق والضغط النفسي لدى طلاب الجامعة، باختلاف متغيري: النوع (ذكرًا/ أنثى)، والفرقة الدراسية (الأولى/ الرابعة)، والتفاعل بينهما"، وتكونت العينة من (ن= 392) طالب وطالبة، ممن تراوحت أعمارهم ما بين(18- 23) سنة، بمتوسط عمري قدره(19,82) سنة، وانحراف معياري قدره (± 0,905)، وقد تم استخدام مقياس الضجر (إعداد: Fahlman et al., 2013، ترجمة: الباحثتين)، ومقياس إدمان الإنترنت: (إعداد Young,1998، ترجمة: الباحثتين)، ومقياس الاكتئاب والقلق والضغوط (إعداد: (Lovibond & Lovibond, 1995، ترجمة: الباحثتين). أوضحت النتائج: وجود تأثيرات مباشرة وغير مباشرة دالة إحصائيًا لإدمان الإنترنت على الضغوط، وعدم وجود تأثير مباشر دال إحصائيًا لإدمان الإنترنت على الاكتئاب والقلق لدى طلاب الجامعة، بينما وجد تأثير غير مباشر بينهم بواسطة الضجر، كما أوضحت النتائج وجود تأثيرات مباشرة دالة إحصائيًا للضجر على الاكتئاب والقلق والضغوط لدى طلاب الجامعة. كما توصلت النتائج إلى عدم وجود فروق دالة إحصائيًا في إدمان الإنترنت والضجر والاكتئاب والقلق وفقًا لمتغيري النوع، والفرقة الدراسية، والتفاعل بينهما، بينما وجدت فروق دالة إحصائيًا في الضغوط وفقًا للتفاعل بين متغيري النوع والفرقة الدراسية؛ حيث ارتفعت مستويات الضغوط بشكل دال إحصائيًا لدى إناث الفرقة الرابعة.The aim of the current research was to identify the direct and indirect effects between boredom (mediating variable), internet addiction (independent variable), and depression, anxiety, and stress (dependent variables) among university students and the extent of the difference between each of: boredom, Internet addiction, depression, anxiety and stress among university students, according to the variables: gender (male/female), academic year (first/fourth), and the interaction between them. The sample consisted of (n=392) male and female students, whose ages ranged between (18-23) years, with an average age of (19.82) years, and a standard deviation of (± 0.905). The Boredom Scale (prepared by: Fahlman et al., 2013, translated by: the researchers), the Internet Addiction Scale (prepared by: Young, 1998, translated by: the researchers), and the Depression, Anxiety and Stress Scale (prepared by: (Lovibond & Lovibond, 1995, translated by: the researchers) were used. The results revealed statistically significant direct and indirect effects of internet addiction on stress, but no statistically significant direct effect of internet addiction on depression and anxiety among university students. However, an indirect effect was found among them through boredom. The results also showed statistically significant direct effects of boredom on depression, anxiety, and stress among university students. The findings also indicated no statistically significant differences in internet addiction, boredom, depression, and anxiety based on gender, academic year, or their interaction. However, statistically significant differences were found in stress based on the interaction between gender and academic year, where stress levels were significantly higher among female fourth-year students.